Ethics and Responsibility of Sellers in Online Buying and Selling: An Analysis of Fiqih Muamalah Muasiroh - Ulfa, Siti Marya (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This study delves into sellers' ethical considerations and responsibilities in online transactions through the lens of contemporary fiqh muamalah. It addresses discrepancies between goods ordered and received, a common catalyst for disputes between sellers and buyers. The research aims to lay a robust groundwork for users of online trading platforms to conduct transactions with integrity. This qualitative research methodology seeks to enrich the understanding of pertinent issues by analyzing relevant texts and leveraging the firsthand experiences of online market participants. The anticipated outcome of this research is to furnish online business operators, consumers, and policymakers with fresh perspectives that enhance the ethicality and accountability of online buying and selling practices. By elevating awareness of their actions' social and moral ramifications, the study aspires to bolster the reputation of online businesses and foster a more integral and sustainable trading milieu. An expansive comprehension of contemporary fiqh muamalah is expected to mitigate misunderstandings and conflicts between sellers and buyers, augmenting trust and equity in online transactions.